Cover Image. (25th July 2022) - Okuyama, Junichi; Watabe, Akemi; Takuma, Shunichi; Tanaka, Kentaro; Shirai, Kotaro; Murakami‐Sugihara, Naoko; Arita, Mamiko; Fujita, Kento; Nishizawa, Hideaki; Narazaki, Tomoko; Yamashita, Yoshiya; Kameda, Kazunari
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13531 "Latitudinal cline in the foraging dichotomy of loggerhead sea turtles reveals the importance of East China Sea for priority conservation" by Okuyama et al. An loggerhead sea turtle (Caretta caretta) nesting at Okinoerabu Island, Japan. Image credit: Junichi Okuyama.